Praktik Penyelenggaran Jenazah di Desa Mu’alaf Provinsi Kalimantan Tengah: Practice of Preserving Bodies in Mu'alaf Village, Central Kalimantan Province - Sanawiah, Sanawiah; Rahmaniati, Rita; Nurbudiyani, Iin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The service activity aims to provide an understanding of the procedures for the burial of corpses, starting from washing and shrouding them to interceding the corpse properly and correctly by Tarjih Muhammadiyah's instructions, as well as equipping 'Aisyiyah Branch Leaders in the Lake Monitoring Village to be skilled in practicing funeral arrangements. The target participants for the service activities are Muslim village residents, especially mothers who actively organize recitations at the Al-Hijrah Mosque. Service activities will be carried out in September 2023 in Daau Pantau Village, Timpah District, Kapuas Regency, located at the Al-Hijrah Mosque. The service was conducted by inviting community leaders from Lake Pantau village and 20 people from religious studies to participate in community service activities. This activity was carried out in two stages: the presentation of material in the form of a lecture and the practice of burial of corpses. Based on the evaluation, the activity was successful in providing an understanding of the procedures for administering corpses starting from washing and shrouding the body to praying the corpse properly and correctly by Tarjih Muhammadiyah's instructions. Furthermore, evaluation of the success of this service through oral tests and the results of the practice showed that, on average, participants could answer questions and practice well.